Faktor Yang Mempengaruhi Perilaku Pembelian Konsumen Berbelanja Di Pasar Modern. - TANJUNG, AFRIA DONI (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
The purpose of this study was to determine factors that influence the behavior of consumers shopping in the modern market. The sample in this study amounted to 100 respondents, people who shop at Modern Market. The data used is primary data and data sekumder. Data analysis technique used in this study is a qualitative descriptive analysis. The results showed that family factors are factors eksteren that social class is the most influential factor in the behavior of consumers shopping at Modern Market, the effect of 7.70%, while the influence of cultural factors 7:50%, personality 5:50%, the role of 4:40%, as well as motivational factors and each reference class is 2:10% and 0.8%. It can be concluded that consumers in making purchasing decisions in the modern market is influenced by cultural,social class, motivation and personality